2010
DOI: 10.1007/s11845-010-0528-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting return to driving post-stroke

Abstract: A relatively high level of return to driving can be achieved post-stroke with a pro-active approach to driver assessment and rehabilitation. A structured assessment and referral programme should be offered where appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 18 publications
2
17
0
Order By: Relevance
“…It revealed that approximately 64% of first-ever stroke patients returned to driving before 12 months after stroke. This percentage is higher than previous studies on return to driving 1 year after stroke (16,17,28), but is consistent with some other studies (21,29). In these studies, patients who received inpatient rehabilitation services or cross-sectional status will probably have had more severe stroke than those who received acute care only, thus leading to a lower rate of return to driving.…”
Section: Discussionsupporting
confidence: 89%
“…It revealed that approximately 64% of first-ever stroke patients returned to driving before 12 months after stroke. This percentage is higher than previous studies on return to driving 1 year after stroke (16,17,28), but is consistent with some other studies (21,29). In these studies, patients who received inpatient rehabilitation services or cross-sectional status will probably have had more severe stroke than those who received acute care only, thus leading to a lower rate of return to driving.…”
Section: Discussionsupporting
confidence: 89%
“…One explanation for this may be that the average age of referred men was lower than that of women. The younger the patient, the more likely he/she is to still be driving [22], and vision assessment is crucial in determining ability to drive. This is unfortunate as age is often used as a poor surrogate marker for pre-morbid function and – maybe more importantly – since diagnosing visual field impairments in an elderly population could prevent falling and further injury [9].…”
Section: Discussionmentioning
confidence: 99%
“…Thematic analysis revealed that valued activities could be divided into the following categories: reengagement in valued activities in general (studies about outdoor and indoor activities); 22,25,26,32,33,3546,48,6064,6772 social and community reengagement (studies about social activities outside the home and in the community); 21,23,27, 28,34,47,50,52,55,58,73,74 mobility (studies about moving around as a meaningful activity) 29,51,53,54,56,57,59 and work. 24,49,65,66,7586 Some single remaining studies on activities such as eating, exercise or leisure …”
Section: Resultsmentioning
confidence: 99%